Spermicidal, Antifertility and Contraceptive Effect of Azadirachta indica A. Juss. Seed Extract in Female and Male Wistar Rats - MacDonald Idu; Sharon Ogedegbe-George; Precious Eromosele Oriarewo; Benjamin Ogunma Gabriel (Biology, Medicine, & Natural Product Chemistry, 2023)
This study investigates the spermicidal and contraceptive effect of Azadirachta indica seed aqueous extract in male and female Wistar rats. The animals were divided into four groups (n=6), graded doses (2.5, 5, and 10 mg/kg) of the extract. They were exposed to female rats in a ratio of 2:1 after 24 hours, 7, and 14 days of administration. The spermicidal properties were evaluated. The female contraceptive study involved 14 days of pre-coital and post-coital administration of the neem seed extract, and contraceptive indexes were investigated. The results obtained from the spermicidal activity showed a significant decrease in male hormonal levels at 2.5, 5, and 10 mg/kg of A. indica (0.73, 0.50, and 1.08 ng/ml); and the sperm cells (102.5, 111.5, and 97 counts) after 24 hours. Administration and mating, compared to the control. Also, the histopathology of the testes showed normal testicles. The contraceptive study elicited a significant decrease in estrogen (1.46 ng/ml), luteinizing hormone (0.094 mg/dl) and progesterone (1.82 ng/ml), at 5 mg/kg in day 14 post-coital study compared with the control. The histopathology of the treated uterus had no deteriorating effect compared with the control. The extract elicited spermicidal and contraceptive potential at a reduced dose, validating its folklore claim.